Ensino de habilidades necessárias em empregos para adolescentes e adultos com TEA: Uma Revisão Sistemática da Literatura: Ensino de habilidades vocacionais para pessoas com TEA (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
Behavioral-analytic research has been developed to teach skills and reduce behavioral excesses in people diagnosed with ASD. In order to understand which interventions are used to include such people with ASD in vocational environments, this study mapped the literature by conducting a systematic literature review based on PRISMA. The Wiley, PubMed and ERIC databases referring to the period from 1968 to 2023 were consulted. Out Off the total documents identified, only 14 met the eligibility criteria. These such studies were analyzed considering the profile of the participants, type of intervention, target behavior, main results and measures of social validation, maintenance, and generalization. It was observed that the teaching of labor skills has been implemented using video modeling, however such studies are still scarce. Finally, future research on the subject is suggested.